1997
DOI: 10.1177/0256090919970108
|View full text |Cite
|
Sign up to set email alerts
|

A Note on HRD Climate

Abstract: Based on the responses of 132 executives of a large public sector heavy engineering organization located in Karnataka, this study attempts to analyse the major factors that are conductive to the development of HRD climate and concludes that early identification of human resource potential and development of skill are the two major tasks of HRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…No significant difference in the perception of HRD Climate was found between the knowledge workers in an engineering institute and a public sector organization (Rodrigues, 2005). The existence of favorable HRD Climate was reported in a study on private sector undertaking in India (Venkateswaran, 1997). Also Famina (2009) in a research on South Asian public sector organization, Kerala State Financing Enterprise, concluded the overall HRD Climate level to be satisfactory.…”
Section: Hrd Climatementioning
confidence: 97%
“…No significant difference in the perception of HRD Climate was found between the knowledge workers in an engineering institute and a public sector organization (Rodrigues, 2005). The existence of favorable HRD Climate was reported in a study on private sector undertaking in India (Venkateswaran, 1997). Also Famina (2009) in a research on South Asian public sector organization, Kerala State Financing Enterprise, concluded the overall HRD Climate level to be satisfactory.…”
Section: Hrd Climatementioning
confidence: 97%
“…Regarding the level of HRD climate prevalent in Indian organizations, different researchers have different views. Some researchers found low to moderate level (Pillai, 2008; Rao & Abraham, 1986; Rao, 1992; Srimannarayana, 2001), whereas some researchers found this level as good (Agarwal, 2002; Mishra & Bhardwaj, 2002; Srimannarayana, 2009; Venkateswaran, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%